Preparation method and application of aerogel for selectively separating radionuclide cesium in water

Preparation of PB/MoS2/GO aerogel by hydrothermal method solves the problems of low efficiency and insufficient stability in the removal of cesium in wastewater by the prior art, and achieves efficient and selective adsorption of cesium ions, which is suitable for a wide range of wastewater treatment applications.

CN119733491AActive Publication Date: 2025-04-01CHANGZHOU UNIV +1

Patent Information

Application Number
CN202411902776.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency, insufficient stability, limited scope of application and secondary pollution risk in removing radionuclides in wastewater.

Method used

PB/MoS2/GO aerogel was prepared by hydrothermal method, and the dispersion of MoS2 was enhanced by GO as a carrier, and the cubic lattice structure of PB and the sulfur group of MoS2 were used to significantly improve the enrichment performance of aerogel on cesium.

Benefits of technology

It achieves efficient, fast and selective adsorption of cesium ions, with ultra-high specific surface area, chemical stability and excellent selection separation performance, and is suitable for the treatment of simulated wastewater and actual seawater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733491A_ABST
    Figure CN119733491A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of wastewater treatment technology and energy conservation and environmental protection, and particularly relates to a preparation method and application of aerogel for selectively separating radionuclide cesium in water. The preparation method comprises the following steps: preparing graphene oxide by using a hydrothermal technology, preparing molybdenum disulfide / GO aerogel by using a hydrothermal synthesis and ultrasonic technology, and inlaying and growing Prussian blue (PB) on the surface of the aerogel, so that the problems that PB and MoS2 are easy to agglomerate and difficult to recover are solved, the GO aerogel is endowed with multiple functions, and the constructed PB / MoS2 / GO aerogel is used for selectively separating radionuclide cesium in water. The selective separation performance of the aerogel on the radionuclide cesium in water under different conditions is investigated, efficient enrichment and recovery of the radionuclide cesium are effectively realized by utilizing the ultralight and highly porous characteristics of the aerogel, and the application potential of the aerogel in the aspects of reducing secondary pollution and improving the environmental treatment effect is proved. An efficient and environment-friendly solution is provided for radionuclide wastewater treatment, and the method has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to an aerogel preparation method for selectively separating radioactive nuclide cesium in water and an application thereof. Background Art

[0002] Radioactive nuclide cesium is the main component of radioactive wastewater. It comes from uranium nuclear fission and is the main source of radiation. Cesium in wastewater mainly exists in the form of ions, which have high biological toxicity, strong migration ability, high radioactivity and long half-life. If it is released directly into the natural environment without safe treatment, it is easy to enter the human body through the food chain. Cesium mainly accumulates in muscles and bones and can cause cancer, leukemia, genetic diseases, etc. At present, adsorption separation technology has attracted much attention due to its high efficiency and simplicity. MoS2 is a graphene-like two-dimensional transition metal sulfide with a unique sandwich structure of three stacked atomic layers (S-Mo-S). According to the Lewis acid-base principle, the sulfur groups rich on its surface and edges act as Lewis bases and can form coordination complexes with cesium ions, thereby enhancing its ability to enrich cesium. However, the powdery form of MoS2 makes it easy to agglomerate and poorly dispersed in water, affecting its application effect. PB is a multifunctional adsorbent that can selectively remove radioactive cesium. Due to the arrangement of iron atoms and ferrous ions in its cubic lattice structure, it exhibits excellent cesium ion adsorption capacity. However, the agglomeration of PB and its separation after use have become application bottlenecks.

[0003] Aerogels, due to their high porosity, low density and large specific surface area, can effectively capture and separate various target substances, such as heavy metal ions, organic pollutants, etc., through specific surface modification and functionalization. The magnetic PB / Fe3O4 / MoS2 composite material mentioned in the published patent CN202210453266.6, although also involving the removal of heavy metal ions, focuses on the utilization of magnetic characteristics. This material may show a certain convenience in the recycling process, but due to its lack of ultra-high specific surface area and porous structure, the adsorption performance is reduced. The adsorption amount of PB / MoS2 material is only about 10 mg / g, and the adsorption equilibrium time is long. In addition, the PB / Fe3O4 / MoS2 magnetic composite has some restrictive disadvantages in environmental remediation and water treatment applications. Its insufficient oxidation stability may lead to a decrease in magnetic properties; there is a risk of secondary pollution, and free iron ions may have a negative impact on the environment; it is sensitive to acid-base environments, which limits its scope of application. GO is a carbon-based material with a high specific surface area and rich oxygen-containing functional groups. These hydroxyl and carboxyl groups make it extremely hydrophilic in water. Its layered structure enables it to effectively adsorb a variety of pollutants when interacting with water molecules, thereby purifying wastewater pollution. However, its selectivity for pollutants is poor, which limits its further application. It is worth noting that the combination of MoS2-PEI and GO is demonstrated in patent CN202311242446.0, and ZIF-8 is further grown by hydrothermal method. Although this method enables aerogels to obtain higher specific surface area and porosity, it may be insufficient in terms of functionalization, especially the selective binding performance with specific radionuclides (such as cesium) and the greater adsorption capacity have not been fully utilized.

[0004] Therefore, considering the limitations of GO, MoS2 and PB and the urgency of removing harmful radioactive nuclides such as cesium, it is planned to construct PB / MoS2 / GO aerogels with ultra-high specific surface area, chemical stability and excellent selective separation of cesium, aiming to give full play to their respective advantages in wastewater treatment, especially in the removal of radionuclides. That is, GO is used as a carrier to enhance the dispersibility of MoS2, while the high specific surface area of ​​GO is combined to improve the overall adsorption performance. At the same time, according to the Lewis acid-base principle, the rich sulfur groups on the surface and edge of the aerogel can significantly improve its enrichment performance for radioactive nuclides such as cesium. In addition, PB is introduced into the composite aerogel, and the high specific surface area and porous structure of the aerogel enable it to provide a large number of growth sites, which is conducive to the enrichment and capture of radionuclides. Through the synergistic effect between the three materials, not only can the efficiency of wastewater treatment be improved, but also a new solution for the separation and recovery of radionuclides can be provided. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an aerogel for selectively separating radioactive nuclides cesium in water and its application, to construct a PB / MoS2 / GO aerogel with ultra-high specific surface area, chemical stability and excellent selective separation performance as an adsorbent for use in the treatment of cesium-containing wastewater, to separate cesium ions through selective separation technology, to solve the problem of radioactive wastewater treatment, and has good application prospects.

[0006] The present invention provides an aerogel preparation method for selectively separating radioactive nuclides cesium from water and its application, comprising the following steps: S1. MoS2 / GO aerogel is prepared by a hydrothermal method. GO dispersion and MoS2 dispersion are mixed by ultrasonication, and then polyacrylic acid aqueous solution and H2O2 solution are added to react at high temperature, cooled to room temperature to obtain MoS2 / GO hydrogel, and freeze-dried to obtain MoS2 / GO aerogel; S2, add MoS2 / GO hydrogel to the mixture of ferric chloride and citric acid, take it out after a period of reaction, then add the mixture of potassium ferrocyanide and citric acid, take it out and wash it after the reaction is completed, repeat this process 1 to 3 times, and obtain PB / MoS2 / GO aerogel after freeze drying.

[0007] Preferably, the concentration of the GO dispersion is 5 mg / mL; the concentration of the MoS2 solution is 2 mg / mL, the concentration of the polyacrylic acid aqueous solution is 1 mg / mL, and the mass fraction of the H2O2 solution is 30%; the volume ratio of GO dispersion: MoS2 solution: polyacrylic acid aqueous solution: H2O2 solution is 5~10:6~12:0.5~1:1.5~3.

[0008] Preferably, the GO dispersion and the MoS2 dispersion are mixed by ultrasonication for 1-1.5 h, and then H2O2 solution is added, and then the polyacrylic acid aqueous solution is added and transferred to a high-temperature hydrothermal autoclave at 180° C., and the reaction time is 7-9 h.

[0009] Preferably, in the mixture of potassium ferrocyanide (K4[Fe(CN)6]) and citric acid, the molar ratio of K4[Fe(CN)6] to citric acid is 1:0.05; in the mixture of ferric chloride and citric acid, the molar ratio of FeCl3 to citric acid is 1:0.05.

[0010] Preferably, the mixture of ferric chloride and citric acid is prepared by mixing 1 mmol FeCl3 and 0.05 mmol citric acid in 20 mL deionized water and stirring magnetically for 0.5 h; the mixture of potassium ferrocyanide (K4[Fe(CN)6]) and citric acid is prepared by mixing 1 mmol K4[Fe(CN)6] and 0.05 mmol citric acid in 20 mL deionized water and stirring magnetically for 0.5 h.

[0011] Furthermore, in step S2, the K4[Fe(CN)6] mixed solution is allowed to stand for 1 to 2 h for adsorption reaction.

[0012] Furthermore, in step S2, the FeCl3 mixed solution is allowed to stand for adsorption reaction for 1 to 1.5 h.

[0013] Preferably, the molar ratio of MoS2 to potassium ferrocyanide or ferric chloride is 0.1-0.2:1-3.

[0014] Preferably, the freeze-drying temperature is -50 ~ -60 ° C, and the vacuum degree is 23 Pa.

[0015] The preparation method of PB / MoS2 / GO aerogel is simple. It can be prepared by sequential adsorption of FeCl3 and K4[Fe(CN)6]. It has good high temperature resistance and excellent adsorption capacity, and is a good adsorbent. In addition, the prepared aerogel has an interconnected porous structure, ultra-light weight, greatly improved water stability, and excellent cesium adsorption selectivity. Its excellent performance in efficient, rapid, and selective adsorption of cesium in simulated wastewater and actual seawater fully demonstrates its practical application potential.

[0016] More importantly, in the present invention, PB nanoparticles are uniformly embedded in the MoS2 / GO aerogel matrix and can contact with cesium ions in the wastewater, which greatly improves the adsorption effect and further enhances the aerogel's ability to treat cesium-containing wastewater.

[0017] In the present invention, PB / MoS2 / GO aerogel is used as an adsorbent to adsorb cesium-containing wastewater.

[0018] Furthermore, PB / MoS2 / GO aerogel is highly stable in a wide pH range (2≤pH≤11), has a high cesium adsorption capacity (84.98 mg / g), and can reach adsorption equilibrium within 0.5 h.

[0019] The second object of the present invention is to provide an adsorbent having selective adsorption for cesium ions and having the same adsorption effect.

[0020] The above technical objectives of the present invention are achieved by the following technical solutions: The present invention provides an application method of PB / MoS2 / GO aerogel for selectively separating cesium from wastewater, specifically, the PB / MoS2 / GO aerogel is put into the cesium-containing wastewater to be treated, put into a constant temperature oscillator for oscillation for 24 to 25 hours, take out the screw bottle, collect the supernatant and filter it, and determine the concentration of cesium in the filtrate. The adsorption efficiency of cesium by PB / MoS2 / GO aerogel is calculated.

[0021] In summary, the present invention has the following beneficial effects: (1) The prepared PB / MoS2 / GO aerogel has large pores and low density. PB nanoparticles are successfully embedded on the surface. It has good cesium ion selective separation performance, with an adsorption capacity of 84.98 mg / g and a wide applicable pH range.

[0022] (2) The synthesis technology of PB / MoS2 / GO aerogel is simple, the application method is easy, it is low-consumption, energy-saving and environmentally friendly, it can be recycled and reused, and it has a good purification effect on cesium-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a physical photo of PB / MoS2 / GO aerogel; Figure 2 It is the SEM image of PB / MoS2 / GO aerogel; Figure 3 XRD patterns of GO aerogel, MoS2 / GO aerogel, and PB / MoS2 / GO aerogel; Figure 4 The selective removal performance of GO aerogel, MoS2 / GO aerogel, and PB / MoS2 / GO aerogel on cesium at different concentrations; Figure 5 The selective removal performance of cesium by GO aerogel, MoS2 / GO aerogel, and PB / MoS2 / GO aerogel at different times; Figure 6 The selective removal performance of cesium by GO aerogel, MoS2 / GO aerogel, and PB / MoS2 / GO aerogel at different pH values; Figure 7 The selective removal performance of cesium in different ions by PB / MoS2 / GO aerogel. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Embodiment 1:

[0025] S1. GO was synthesized by Hummers oxidation method. First, 23 mL of concentrated sulfuric acid was added to a 250 mL beaker under ice bath, and then 0.5 g of graphite powder and 0.5 g of NaNO3 were slowly added under mechanical stirring, and then 3.0 g of K2MnO4 was slowly added and mechanical stirring was continued for 1 h; graphite powder, NaNO 3、The mass ratio of K2MnO4 is: 1:1:6. Then, transfer the beaker to an oil bath at 35°C, stir for 2 h, slowly add 46 mL of deionized water to the flask, quickly raise the oil bath temperature to 90°C, stir for 30 min, add 100 mL of deionized water and 3 mL of H2O2 (30 wt%), stir evenly and terminate the reaction. The reaction solution is bright yellow. Subsequently, wash away the residual metal ions with a 5wt% dilute HCI solution, and then wash repeatedly with deionized water until neutral. Finally, disperse the obtained product in 50 mL of deionized water and ultrasonicate for 2 h to obtain a GO dispersion. S2, 1.249 g ammonium molybdate ((NH4)6Mo7O2·4H2O) and 2.303 g thiourea (CH4N2S) were dissolved in 35 mL deionized water and stirred vigorously for 30-40 min. Then, the mixed solution was transferred to a 50 mL reactor and heated to 200 °C for 24 h. After cooling naturally to room temperature, the black product was rinsed with deionized water and ethanol several times, and then freeze-dried (-55 °C, 48 h) to obtain MoS2 nanosheets; S3, GO dispersion (10 mL, 5 mg / mL) and MoS2 (12 mL, 2 mg / mL) were mixed by ultrasonication for 1 h, and then H2O2 solution (30wt%; 3 mL) was added, and then polyacrylic acid aqueous solution (1 mL, 1 mg / mL) was added and transferred to a high-temperature hydrothermal autoclave (180 °C, 8 h). MoS2 / GO aerogel was prepared by hydrothermal method and freeze-dried for 24 h to obtain MoS2 / GO aerogel; S4, 1 mmol FeCl3 and 0.05 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. 1 mmol K4[Fe(CN)6] and 0.05 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. The mass of K4[Fe(CN)6] was 0.42239 g, the mass of FeCl3 was 0.2703 g, and the mass of citric acid was 0.0105 g. The MoS2 / GO hydrogel in S3 was placed in a mixed solution of 1 mmol FeCl3 and 0.05 mmol citric acid. After reacting for 1 h, it was taken out and placed in a mixed solution of 1 mmol K4[Fe(CN)6] and 0.05 mmol citric acid. The reaction continued for 2 h. The loading process was repeated three times. Then it was taken out and freeze-dried for 24 h to obtain PB / MoS2 / GO aerogel.

[0026] The application method is as follows: Take 10 mg of PB / MoS2 / GO aerogel from Example 1, add it into a 20 mL system with a cesium concentration of 50 mg / L solution, place it in a shaker (120 r / min, 25°C) for 12 h of oscillation adsorption, and the cesium removal rate in the cesium-containing wastewater can reach 92.20%. After adsorption, the PB / MoS2 / GO aerogel is separated by simple suspension.

[0027] Figure 1 This is a real photo of PB / MoS2 / GO aerogel; the appearance of PB / MoS2 / GO aerogel is as follows Figure 1 As shown in the figure, it contains more pores and is light in texture, so it can be easily placed on dandelion flowers. In addition, the density of PB / MoS2 / GO aerogel is calculated by direct weighing method to be in the range of 14.16~16.66 mg.cm -3 The aerogel density is lower than that of water.

[0028] Figure 2 It is the SEM image of PB / MoS2 / GO aerogel; Figure 2 The morphology of PB / MoS2 / GO aerogel was characterized by SEM. The results showed that there were a large number of holes on the surface of PB / MoS2 / GO aerogel, and the pores were obvious, arranged irregularly in a honeycomb shape, and the pore walls were cross-linked and staggered. In addition, many cubic particles were embedded on the pore walls, which was mainly due to the growth of Prussian blue on the surface of the aerogel. The particle size of Prussian blue was about 100 nm.

[0029] Figure 3 is the XRD pattern of PB / MoS2 / GO aerogel; Figure 3 The crystal structure and phase composition of GO, MoS2 / GO and PB / MoS2 / GO aerogels were analyzed by XRD. Figure 3It is shown in the figure that an obvious diffraction peak corresponding to GO is observed at 2θ = 25.8°, indicating that GO retains the physical and chemical properties of natural graphite. Compared with GO aerogel, MoS2 / GO aerogel has new diffraction characteristic peaks at 9.1°, 32.1° and 57.2°, which correspond to the (002), (100) and (110) crystal planes of MoS2, respectively. These findings are consistent with the MoS2 standard card, confirming that MoS2 has been successfully synthesized in the aerogel. Moreover, PB / MoS2 / GO aerogel not only has the diffraction characteristic peaks of MoS2, but also has new additional peaks at 2θ = 17.64° (200), 24.98° (220), 35.58° (400), 39.94° (420) and 43.94° (422), which are mainly from PB with higher crystallinity, further confirming that PB is firmly fixed on MoS2 / GO aerogel. Overall, the XRD analysis provided comprehensive information on the crystalline phases present in the composites, confirming the successful preparation of PB / MoS2 / GO and the stable incorporation of PB on the MoS2 / GO framework. Embodiment 2:

[0030] S1. Synthesis of GO by Hummers oxidation method: same as in Example 1.

[0031] Preparation of S2 and MoS2 nanosheets: same as Example 1.

[0032] Preparation of S3, MoS2 / GO aerogel: same as Example 1.

[0033] S4, 2 mmol FeCl3 and 0.1 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. 2 mmol K4[Fe(CN)6] and 0.1 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. The mass of K4[Fe(CN)6] was 0.84478 g, the mass of FeCl3 was 0.5406 g, and the mass of citric acid was 0.021 g. The MoS2 / GO hydrogel in S3 was placed in a mixed solution of 2 mmol FeCl3 and 0.1 mmol citric acid. After reacting for 1 h, it was taken out and placed in a mixed solution of 2 mmol K4[Fe(CN)6] and 0.1 mmol citric acid. The reaction continued for 2 h. The loading process was repeated three times. Then it was taken out and freeze-dried for 24 h to obtain PB / MoS2 / GO aerogel.

[0034] The application method is as follows: Take 10 mg of PB / MoS2 / GO aerogel from Example 2, add it into a 20 mL system with a cesium concentration of 50 mg / L solution, place it on a shaker (120 r / min, 25°C) for 12 h of oscillation adsorption, and the cesium removal rate in the cesium-containing wastewater can reach 95.20%. After adsorption by PB / MoS2 / GO aerogel, it can be separated by simple suspension. Embodiment 3:

[0035] S1. Synthesis of GO by Hummers oxidation method: same as in Example 1.

[0036] Preparation of S2 and MoS2 nanosheets: same as Example 1.

[0037] Preparation of S3, MoS2 / GO aerogel: same as Example 1.

[0038] S4, 3 mmol FeCl3 and 0.15 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. 3 mmol K4[Fe(CN)6] and 0.15 mmol citric acid were mixed in 20 mL deionized water and magnetically stirred for 0.5 h. The mass of K4[Fe(CN)6] was 1.26717 g, the mass of FeCl3 was 0.8109 g, and the mass of citric acid was 0.0315 g. The MoS2 / GO hydrogel in S2 was placed in a mixed solution of 3 mmolFeCl3 and 0.15 mmol citric acid, and after standing for 1 h, it was taken out and placed in a mixed solution of 3 mmol K4[Fe(CN)6] and 0.15 mmol citric acid, and continued to stand for 2 h. The loading process was repeated three times. Then it was taken out and freeze-dried for 24 h to obtain PB / MoS2 / GO aerogel.

[0039] The application method is as follows: Take Example 3 and add 10 mg of PB / MoS2 / GO aerogel into a 20 mL system with a cesium concentration of 50 mg / L solution. After placing it on a shaker (120 r / min, 25°C) for 12 h of oscillation adsorption, the cesium removal rate in the cesium-containing wastewater can reach 98.20%. After the aerogel is adsorbed, it is separated by simple suspension.

[0040] The conclusions obtained in Examples 1-3 are: PB / MoS2 / GO aerogel exhibits excellent cesium removal performance and effectiveness of the synthesis method. The preparation process of PB / MoS2 / GO aerogel is stable, and its porous structure characteristics are confirmed by SEM and XRD analysis, making it suitable for adsorption materials. The cesium removal rate increases to 92.20%, 95.20% and 98.20% respectively with the increase of FeCl3 and K4[Fe(CN)6]. The low density of this aerogel makes it easy to separate and suitable for various environmental governance applications, especially in the removal of heavy metals. Overall, this study provides theoretical and practical support for the development of new environmental remediation materials, and its application in complex wastewater and economic evaluation can be further explored in the future. Comparative Example 1:

[0041] Compared with Example 1, Comparative Example 1 differs in that only MoS2 / GO aerogel is prepared, and the preparation method of MoS2 / GO aerogel is the same as S1-S3 of Example 1. Comparative Example 2:

[0042] Comparative Example 2 is different from Example 1 in that GO aerogel is prepared. The preparation method of GO aerogel is as follows: after ultrasonicating a GO dispersion (10 mL, 5 mg / mL) for 1 h, a H2O2 solution (30wt%; 3 mL) is added, and then a polyacrylic acid aqueous solution (1 mL, 1 mg / mL) is added and transferred to a high-temperature hydrothermal autoclave (180°C, 8 h). After naturally cooling to room temperature, the mixture is freeze-dried at -56°C for 24 h to obtain GO aerogel.

[0043] Figure 4 The selective removal performance of cesium in different concentrations of PB / MoS2 / GO aerogel, MoS2 / GO aerogel, and GO aerogel; Figure 4It was revealed that PB / MoS2 / GO aerogel, MoS2 / GO aerogel, and GO aerogel showed significant adsorption capacity in removing cesium (Cs) from wastewater; the adsorption amount of PB / MoS2 / GO aerogel increased with the increase of initial cesium concentration, and the surface active sites were abundant at low concentrations (10-40 mg / L), and the adsorption effect was good; when the concentration reached the saturation point (80 mg / L), the adsorption capacity slowed down; and for MoS2 / GO aerogel, the saturation point was reached at a concentration of about 40 mg / L. At this time, the adsorption capacity of PB / MoS2 / GO aerogel (86.51±1.75 mg / g) was significantly higher than that of MoS2 / GO (43.81±3.41 mg / g) and GO aerogel (18.66±0.55 mg / g). The above results show that ① the adsorption capacity of PB / MoS2 / GO aerogel (86.51±1.75 mg / g) is significantly higher than that of the other two materials (MoS2 / GO aerogel, GO aerogel), and the adsorption amount is significantly increased compared with GO aerogel and PB / MoS2 materials. The synergistic effect of PB, MoS2 and GO aerogel enables PB / MoS2 / GO aerogel to have a higher adsorption amount and more effectively selectively capture cesium ions. Compared with the other two materials, the affinity for cesium is significantly improved.

[0044] Figure 5 The selective removal performance of cesium by PB / MoS2 / GO aerogel at different times; Figure 5 The results showed that PB / MoS2 / GO aerogels were superior to GO aerogels and MoS2 / GO aerogels in the adsorption of cesium (Cs), indicating that the incorporation of PB significantly improved the adsorption capacity of aerogels. The adsorption process of PB / MoS2 / GO aerogels was divided into two stages: the initial stage (0-60 minutes) with rapid binding of Cs, followed by an equilibrium stage in which the surface was saturated with Cs. PB / MoS2 / GO aerogels reached adsorption equilibrium within 1 hour, with an equilibrium adsorption capacity of 86.46±2.29 mg / g, which was much higher than that of MoS2 / GO aerogels (44.12±2.79 mg / g) and GO aerogels (15.21±3.12 mg / g). The growth of MoS2 and PB increased the available active sites, enhanced the affinity for Cs, and significantly improved the adsorption performance of GO aerogels for cesium.

[0045] Figure 6 The selective removal performance of cesium by PB / MoS2 / GO aerogel at different pH values; Figure 6The selective adsorption performance of PB / MoS2 / GO aerogel for cesium (Cs) under different pH conditions was shown. The results showed that with the change of pH, the removal rate first increased and then decreased. The optimal removal rate appeared between pH 7 and 8. The adsorption amount reached 117.22±3.52 mg / g at pH 8, indicating that the aerogel had excellent removal effect on Cs in wastewater. The control experiment showed that the equilibrium adsorption capacity of MoS2 / GO aerogel and GO aerogel was 43.81±2.86 mg / g and 18.28±3.07 mg / g, respectively, further confirming the key role of PB and MoS2. The adsorption capacity of PB / MoS2 / GO aerogel can be divided into three stages with the change of pH: at low pH, the adsorption is inhibited due to protonation, the adsorption capacity is enhanced in the neutral to slightly alkaline pH range, and the adsorption amount decreases after exceeding the optimal pH due to anion repulsion.

[0046] Figure 7 The selective removal performance of cesium in different ions by PB / MoS2 / GO aerogel; Figure 7 The study of the selectivity of PB / MoS2 / GO aerogel for cesium ions (Cs) was demonstrated. 2+ 、Na + and Mg 2+ The coexisting metal ions formed different ion mixtures with 50 mg / L Cs solution, maintaining the concentration ratio of metal ions to Cs at 100:1. The results show that in the presence of potassium ions, the adsorption of Cs by PB / MoS2 / GO aerogel is significantly lower than that for other metal ions, the former is 22.36±0.61 mg / g, while the latter exceeds 80 mg / g. Specifically, the adsorption amount of Ca, Na and Mg ions exceeds 80 mg / g when they coexist. This is mainly because the ionic radius of potassium ions is similar to that of Cs ions, which leads to its more effective competition with Cs. However, these results prove that PB / MoS2 / GO aerogel still shows good selectivity for Cs under the competition of multiple metal ions, indicating its potential application value in removing Cs in nuclear wastewater treatment.

[0047] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been presented as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing aerogel for selectively separating radioactive nuclides of cesium in water, characterized in that: The preparation method comprises the following steps: S1. MoS2 / GO aerogel is prepared by a hydrothermal method: GO dispersion and MoS2 dispersion are mixed by ultrasonication, and then polyacrylic acid aqueous solution and H2O2 solution are added to react at high temperature, cooled to room temperature to obtain MoS2 / GO hydrogel, and freeze-dried to obtain MoS2 / GO aerogel; S2. Add MoS2 / GO hydrogel to a mixture of ferric chloride and citric acid, take it out after reacting for a period of time, and then add a mixture of potassium ferrocyanide and citric acid. After the reaction is completed, take it out and wash it. Repeat this process 1 to 3 times, and obtain PB / MoS2 / GO aerogel after freeze-drying.

2. The method for preparing aerogel for selectively separating radioactive nuclides cesium in water according to claim 1, characterized in that: In step S1, the volume ratio of GO dispersion, MoS2 dispersion, polyacrylic acid aqueous solution and H2O2 solution is 5~10:6~12:0.5~1:1.5~3; the concentration of GO dispersion is 5 mg / mL; the concentration of MoS2 dispersion is 2 mg / mL, the concentration of polyacrylic acid aqueous solution is 1 mg / mL, and the mass fraction of H2O2 solution is 30%.

3. The method for preparing aerogel for selectively separating radioactive nuclides cesium in water according to claim 1, characterized in that: The high temperature reaction in step S1 is carried out in a high temperature hydrothermal reactor at 180° C., and the reaction time is 7 to 9 h.

4. The method for preparing aerogel for selectively separating radioactive nuclides cesium in water according to claim 1, characterized in that: In the mixed solution of ferric chloride and citric acid, the molar ratio of FeCl3 to citric acid is 1:0.05; in the mixed solution of potassium ferrocyanide and citric acid, the molar ratio of potassium ferrocyanide to citric acid is 1:0.

05.

5. The method for preparing aerogel for selectively separating radioactive nuclides cesium in water according to claim 1, characterized in that: The molar ratio of MoS2 to potassium ferrocyanide is 0.1~0.2:1~3; the molar ratio of MoS2 to ferric chloride is 0.1~0.2:1~3.

6. The method for preparing aerogel for selectively separating radioactive nuclides cesium in water according to claim 1, characterized in that: In step S2, the reaction is carried out in a mixture of ferric chloride and citric acid for 1 to 1.5 h; and the reaction is carried out in a mixture of potassium ferrocyanide and citric acid for 1 to 2 h.

7. An aerogel for selectively separating radioactive nuclides cesium from water prepared by the method according to any one of claims 1 to 6.

8. The aerogel for selectively separating radioactive nuclides cesium from water prepared by the method according to any one of claims 1 to 6 is used as an adsorbent in the selective adsorption of cesium ions.

9. The use according to claim 8, characterized in that: The pH range for adsorption of cesium ions is 2≤pH≤11.

Citation Information

Patent Citations

  • Preparation method of prussian blue cube / molybdenum disulfide nano composite material

    CN105842438A

  • Preparation method and application of magnetic PB / Fe3O4 / MoS2 composite material

    CN114768749A

  • Complex enzyme and application thereof in chemical immunoluminescence analysis

    CN117347623A

  • Method for producing thin layers

    WO2011144754A2

Cited By

  • Molybdenum disulfide-MXene / biomass carbon composite aerogel as well as preparation method and application thereof

    CN120132813A

  • A molybdenum disulfide-MXene / biomass carbon composite aerogel, a preparation method and application thereof

    CN120132813B